1983
DOI: 10.1007/bf00439263
|View full text |Cite
|
Sign up to set email alerts
|

Functional supersensitivity to adrenergic agonists in the rat after DSP-4, a selective noradrenergic neurotoxin

Abstract: Rats treated with DSP-4 [N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine], a selective noradrenergic neurotoxin, showed no differences compared to control rats in the number of head dips, a measure of exploratory behavior. Since a previous neurochemical investigation had demonstrated that DSP-4 rats have supersensitive alpha 2- and beta-adrenergic receptors in certain regions of the central nervous system, the behavior of these animals was also examined after the injection of clonidine, an alpha 2 agonist, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Recently, it was shown that fl-agonists have an inhibitory action on locomotor activity and exploration (Przegali~ski et al, 1983;Mogilnicka, 1982;Dooley et aL, 1983), suggesting that the salbutamolinduced suppression of exploratory activity in rats can be used as a test for fl-adrenoceptor function (Przegali~ski et al, 1983). These authors found that the suppressive effect of salbutamol was antagonized by chronic treatment with antidepressants.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, it was shown that fl-agonists have an inhibitory action on locomotor activity and exploration (Przegali~ski et al, 1983;Mogilnicka, 1982;Dooley et aL, 1983), suggesting that the salbutamolinduced suppression of exploratory activity in rats can be used as a test for fl-adrenoceptor function (Przegali~ski et al, 1983). These authors found that the suppressive effect of salbutamol was antagonized by chronic treatment with antidepressants.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings lead to similar conclusions: the hyperthermic effect of CLON is mediated by postsynaptic a2-adrenoceptors, since damage to central noradrenergic terminals with a new neurotoxin, DSP-4, does not inhibit the CLON-induced hyperthermia. In fact, an increase in CLONhyperthermic action was observed in DSP-4 lesioned rats, suggesting a supersensitivity of the central a2-receptor in DSP-4-treated rats (Dooley et al, 1983 b).…”
Section: Discussionmentioning
confidence: 98%
“…ClenbuteroMnduced hypoactivity is known to be centrally mediated, since it is abolished after destruction of brain noradrenergic neurons (Dooley et al, 1983) and [32 receptors are known to utilize adenylate cyclase as a second messenger. Since lithium treatment does not affect adrenergic receptor number (Gross et al, 1985), the results of Givant et al (1990) are likely to be due to lithium inhibition of adenylate cyclase, as more directly demonstrated in the present experiment.…”
Section: Discussionmentioning
confidence: 99%